Acceleration Model of Child-Friendly City/District in Lampung Province - Duadji, Noverman; Tresiana, Novita; Putri, Rahmah Dianti (Research and Development Agency Ministry of Home Affairs, 2018)
Lampung Province has issued several children programs, but its implementation is still not maximal. Such conditions are possible because, in the context of the actors and substance, the KLA (Kota Layak Anak or Child-Friendly City) program still positions the local government as a single actor. The issue of children has not been the center of attention in the overall development policy. Sectoral, segmented, and structured children programs do not involve community potential. Such patterns and modeling are the products of top-down planning. That is, the location of the constraints is in the centralized model as the applied planning model. Related to this, hence more comprehensive, integrated methods, models and ways to achieve the objectives of KLA program of Lampung Province are required. The purpose of this study is to explain: 1) various central issues of child’s problems, potentials of community institutional support and 2) model structure and phases of acceleration of city/district proper for children that can fulfill child rights, child protection, and child development. On the basis of the expected objectives, used the descriptive qualitative method. The research findings: 1) there are still many problems that occur in Lampung Province; 2) This study provides an overview of the potential of community institutions that have concerns about child issues and support for local government policy, but both are not synergistic, development programs are still implemented partially, segmented, sectoral, not yet integrated and less involving or inclusive to community potential. It can be concluded that the solution that can be developed is to build a collaborative planning model based on dialogue in multi-stakeholder forums as a strategic material for the city/district in accordance with the implementation of the 3 stages which become the acceleration area of KLA.